PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA BIRO UMUM DAN KEUANGAN UNIVERSITAS LAMPUNG - Apandi Apandi (Center of Language and Cultural Studies, 2018)
This correlational study aims at seeing the effect of leadership style and motivation towards employee performance. A number of 53 sample was selected from General and Finance Bureau at Lampung University. Data were collected using questionnaire and were analyzed using multiple linier regression with the help of SPSS 17.0 statistical software. Result of hypothesis testing shows t-value = 2.374 and t-table = 1.67655. In addition, for the motivation variable on employee performance reveals t-value = 7.283 and t-table = 1.67655. The simultaneous testing altogether obtained statistical results of F-value for 40.288 and F-table = 3.18. The evidence means that there is a significant effect either partially or simultaneously between the leadership style and motivation on employee performance of the General and Finance Bureau of Lampung University.